Política Nacional de Atenção à Saúde Indígena no Brasil: dilemas, conflitos e alianças a partir da experiência do Distrito Sanitário Especial Indígena do Xingu - Araújo, Reginaldo Silva de (2012)
The Brazilian State, in order to start a new political relationship with indigenous communities, implemented, in 1999, the National Policy of Attention to Indigenous Health (PNASPI), through the National Health Foundation (FUNASA) and 34 Special Indigenous Sanitary Districts (DSEIs) located in the national territory. The new health policy for the indigenous areas, structured within the differentiated attention Subsystem and integrated into the Unified Health System (SUS), proposed a participatory model of Civil Society-State comanagement, via council or public policy managers, cooperation agreements with NGOs and other participatory experiences. Just likeit probably occurred in other indigenous territories, the implementation of a new State Agency in the Xingu brought a creative process of political and cultural adaptationto local leaders, generating the possibility of an inter-ethnic negotiation field. It was therefore from this political scenario that the research proposed to understand the indigenous leaders' forms of practice and their representations. Thus, it sought to observe the strategies of the region s representatives who "make pacts" and "negotiate" with the various organizations responsible for the implementation of health public policies (FUNASA, City Halls and NGOs), oriented by constitutional principles that ensure (universal) rights and (differentiated) specificities regarding preventive health care to these and all other indigenous groups within the national territory. The analysis of these forms of organization and political activity also sought to observe how the implementation of the health policy and its institutional arrangements generated a redesigning of the policy practices established between indigenous peoples and the State. Thus, even though indigenous leaders have not articulated a homogeneous position regarding the State's "offer" of partnership through NGOs and management councils,many of which with goals to ensure recognition and political spaces both in the national scene and in their traditional systems of organization, they started a project that pursues the enlargement of the memberships and a change in the organizational structure of the State.The movement, conducted by the leaders of the Alto Xingu, involves a participatory model of comanagement, whose practice does not dispense a few moments of consummation of the identity among the actors who make up this participatory experience.